Apportionment, fiscal equalization and decentralized tax enforcement - Christian Traxler; Andreas Reutter (Max Planck Institute for Research on Collective Goods, 2008)
We study tax evasion and decentralized tax enforcement in a federal economy with mobile capital and the endogenous formation of multiregional companies. Regions use their enforcement policy as a strategic instrument to engage in fiscal competition. Within this framework, we analyze the uncoordinated policy choice under formula apportionment (FA) and compare it to the incentives which derive from fiscal equalization (FE). As both systems redistribute collected revenues but not enforcement costs, they distort the regions' incentives to enforce taxes. At the same time, jurisdictions partially internalize the fiscal externalities caused by their enforcement policy. We show that the tradeoff between these two opposing effects differs between FA and FE, and crucially depends on the degree of interregional firm integration under FA. We discuss conditions under which FA, FE or a joint system of FA cum FE provides the 'best' incentives for decentralized tax enforcement.
Keywords: H77; H71; H26; 330; Tax Enforcement; Tax Evasion; Formula Apportionment; Fiscal Equalization; Tax Revenue Sharing; Steuerfahndung; Steuerwettbewerb; Finanzföderalismus; Finanzausgleich; Steuervermeidung; Theorie